Sustainable development, evaluation and policy making theory, practise and quality assurance - Raggamby, Anneke (Cheltenham Edward Elgar, 2012)
This pathbreaking book contributes to the discourse of evidence-based policy-making. It does so by combining the two issues of policy evaluation and sustainable development linking both to the policy-cycle. It covers contributions
Includes bibliographical references and index
Keywords: Sustainable development -Evaluation.